Assessment of the Pharmacoeconomic Impact of Reusing Overfill Prescription Medicines with Closed Dose - Moreno Araujo, Lorenna; Roldão da Silva, Edvan; de Souza Alves, Felipe; Françozo de Melo, Adriana; Soares dos Santos, Fred (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To evaluate the financial impact and reduction of waste by reusing leftover prescription medication bottles with flat doses in an oncology clinic in the Federal Dis-trict. Methods: Descriptive, retrospective study, from the period between June 2020 and June 2023, on the amount of average overfill per vial of pembrolizumab, pertuzu-mab, atezolizumab and daratumumab SC prescribed in closed doses using closed system devices.The manipulations were carried out under controlled temperature conditions, a clean area environment and validation carried out by 3 pharmacists. Results: 121 vials of pembrolizumab (R$ 2,207,675.25) were saved out of 4,656 used, 20 vials of pertuzumab (R$ 267,084.80) out of 564 used, 7 vials of atezolizumab 1200 mg (R$ 150,172.26) in 452 used, 25 bottles of atezolizumab 840 mg (R$ 766,184.75) in 139 bottles used, 12 bottles of daratumumab SC (R$ 328,514.28) in 292 used, totaling R$ 3,719,631.34 in cost reduction in this period, using the cost price as a reference, such as the Brasíndice Factory Price, and closed system security devices. Conclusion: The use of a closed system device, combined with clean area validation, pharmaceutical asepsis techniques and good handling practices, allows the use of closed dose medica-tions within 7 days. Considering the volume of manipulations, it is possible to optimize resources and generate savings over accumulated periods. The pharmacist’s technical knowledge combined with financial management concepts contributes significantly to the sustainability of institutions.